Reaktualisasi Ahimsa dalam Perdamaian Agama di India : Kritik atas Otoritarianisme Agama dalam Pemikiran Gandhi - Abdul Kodir; Ahmad Qiram As-Suvi; Faizah Ukhti Rianda (Pustaka Peradaban, 2023)
This article aims to describe religious authoritarianism in India towards Muslim groups and the important role of the concept of ahimsa in creating interfaith peace in India. The research was conducted using a qualitative approach with a literature review. The data sources used include texts, manuscripts, documents, and literature that discuss religious authoritarianism in India and Gandhi's thoughts on the concept of ahimsa. The results of this study indicate that the concept of ahimsa, which is the principle of non-violence espoused by Gandhi, has strong relevance in dealing with religious authoritarianism in India. Ahimsa is a catalyst that promotes religious peace by emphasizing the importance of mutual respect, dialogue, tolerance, and peaceful conflict resolution. It is hoped that the results of this research can become a basis for promoting religious harmony and reducing religious tensions, especially in India.